PERAN PASAR TEMATIK DALAM MENOPANG KESEJAHTERAAN MASYARAKAT JAKARTA - Meliana, Vina; Lestari, Diyan; Rahmanto, Basuki Toto (Economic Faculty, Attahiriyah Islamic University, 2020)
Purpose- This study aims to analyze the role of the thematic market on society's prosperity in Jakarta. Design/methodology/approach- The respondent of this study is the seller who sells their products in Jakarta thematic market. Multiple linear regression is used as a data analysis method. Findings- The result of this study state that innovation does not affect the prosperity of Jakarta society, while brand image affects the prosperity of Jakarta society. Implications- Traditional market conditions with minimal facilities make most consumers reluctant to allocate a lot of time in the market. Thus, even though the thematic market is a traditional market, it must be managed in such a way with facilities that enable consumers to spend a long time in the market. Keywords: Innovation, Brand Image, Prosperity